The future of evolutionary economics: Why modalities matter - Ulrich Witt (Max Planck Institute of Economics, 2013)
The label "evolutionary" is currently used in economics to describe a variety of theories and topics. Far from inspiring the paradigmatic shift envisioned by some of the early proponents of evolutionary economics, the patchwork of theories and topics in this field demonstrates the need of an overarching interpretative frame. In other disciplines, the adoption of the Darwinian theory of evolution extended by hypotheses on cultural evolution has led to such a paradigm shift. This paper explores what can be accomplished by adopting that theory as an interpretative frame also for economics. Attention is directed in particular to the modalities of causal explanations that are germane to such a frame. The relevance of these modalities to the various thematic and theoretical specializations carrying the label "evolutionary" in economics is established to demonstrate the suitability as a common frame. Moreover, these modalities suggest a criterion on the basis of which evolutionary research can be distinguished from non-evolutionary research in economics. The case of institutional economics is used to outline some implications in an exemplary fashion.
Keywords: 330